(untitled) (Proceedings OPTIMAL, 2025)
Background: Hypertension is a leading non-communicable disease globally, particularly prevalent among older adults. Despite the effectiveness of non-pharmacological strategies such as dietary modification in managing hypertension, adherence remains a major challenge. Family support has been identified as a critical factor influencing adherence, yet the extent and mechanisms of this relationship remain underexplored. Objective: This literature review aims to systematically examine empirical evidence on the relationship between family support and dietary compliance in elderly individuals diagnosed with hypertension. Methods: A structured literature review was conducted using the Joanna Briggs Institute (JBI) framework. A comprehensive search across databases—PubMed, Google Scholar, ScienceDirect, DOAJ, Portal Garuda, Microsoft Academic, and PNRI—was performed using the PICOST strategy. Inclusion criteria focused on studies published between 2016–2021, involving elderly hypertensive patients, examining family support as an intervention, and assessing dietary compliance. Results: Nine studies met the eligibility criteria. The majority demonstrated a positive association between family support and adherence to dietary recommendations. Emotional, informational, and instrumental supports were found to significantly influence dietary behaviors. While instrumental support appeared most impactful, emotional support alone showed inconsistent results. Heterogeneity in methodology, sample size, and operationalization of family support highlighted the need for further standardized investigations. Conclusion: Family support, particularly instrumental forms, plays a significant role in enhancing dietary compliance among older adults with hypertension. Tailored family-centered interventions that respect cultural values are recommended to improve dietary adherence and health outcomes in this population. Keywords: hypertension, dietary compliance, elderly, family support, adherence, literature review